Comparison of static friction and surface topography of low friction and conventional TMA orthodontic arch wires: An in-vitro study - Nouf Alsabti (Saudi Dental Journal, 2021)
Background: Arch wire surface characteristics, especially surface roughness and topography, influence the coefficient of friction during sliding. The clinician should be familiar with the properties of orthodontic appliances and materials that could result in high friction to maximize the efficiency of treatment. This study aimed to compare the static friction of orthodontic arch wire materials, including a newly introduced low-friction TMA, conventional TMA, and stainless steel arch wires, using an Instron universal testing machine and to evaluate their surface topographical features using a noncontact optical profilometer. Methods: A total of 30 arch wire specimens were used, including 10 low-friction TMA (TMA-Low), 10 conventional TMA (TMA-C), and 10 stainless steel (SS), (Ormco, Orange, CA, USA) measuring 0.016 × 0.022 in. The static frictional force of each arch wire material was measured using the universal Instron machine. The surface topography was evaluated using a noncontact profilometer machine. Results: The static frictional resistance forces were highest in the TMA-C alloy group, and the value was statistically significant in comparison to the SS arch wire but not to the TMA-Low arch wire. The mean value of the static friction of the TMA-Low group was intermediate between the TMA-C and SS arch wires. However, this difference was statistically insignificant compared to the other two alloys. A surface roughness evaluation using a profilometer machine revealed that the highest mean of all three roughness parameters was found in the TMA-C group, followed by the TMA-Low and SS arch wires in descending order. Conclusion: The static friction resistance forces and surface roughness values of the TMA-Low arch wire are comparable to those of TMA-C but are still considered inferior to those of the SS arch wire.